Okręg Nowogródek Armii Krajowej .......... 373 - Dudek, Tomasz (Kresowi żołnierze Armii Krajowej: Historia – Polityka – Pamięć, 2024)
THE NOVOGRUDOK HOME ARMY DISTRICTThis section discusses the history of the ZWZ-AK (The Home Army Union of Armed Struggle) in its Novogrodek district during World War Two. In this paper, the author attempted to showcase the operations of individual units of the Polish underground resistance organisation in the Novogrudok area which targeted the Soviets and the Germans. The author pointed to the fact of a regular Polish vs. Soviet guerilla warfare that raged since 1943 in the area. The Soviets were engaged by the Home Army 77th Infantry Regiment and the Stowbtsy Combat Group (Polish: Zgrupowanie Stołpeckie). The author attempted to reconstruct the staffing of individual underground resistance structures in the Novogrudok area and showcased the course of Operation Ostra Brama (Operation Gate of Dawn, or the retaking of Vilnius) by the joint forces of the Home Army Vilnius and Novogrudok Districts. The section culminates in a discussion of the Polish underground resistance in the Novogrudok area after Operation Ostra Brama. The author points out that the last Home Army operatives held out in the area up to the early 1950s.